Systemic inflammation markers and the prevalence of hypertension: A NHANES cross-sectional study - Xu, Jun-Peng; Zeng, Rui-Xiang; Zhang, Yu-Zhuo; Lin, Shan-Shan; Tan, Jia-Wei; Zhu, Hai-Yue; Mai, Xiao-Yi; Guo, Li-Heng; Zhang, Min-Zhou (Hypertension research, 2023)
Systemic inflammation markers have been highlighted recently as related to cardiac and non-cardiac disorders. However, few studies have estimated pre-diagnostic associations between these markers and hypertension. In the National Health and Nutritional Examination Survey from 1999 to 2010, 22,290 adult participants were included for analysis. We assessed associations between four systemic inflammation markers based on blood cell counts: systemic immune-inflammation index (SII), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), and hypertension prevalence in multivariate logistic regression analysis with odds ratio (OR) and 95% confidence interval (CI). To further explore their associations, subgroup and sensitivity analyses were performed. In continuous analyses, the ORs for hypertension prevalence per ln-transformed increment in SII and NLR were estimated at 1.115 and 1.087 (95% CI: 1.045-1.188; 1.008-1.173; respectively). Compared to those in the lowest tertiles, the hypertension risks for subjects in the highest SII and NLR tertiles were 1.20 and 1.11 times, respectively. Conversely, we found that PLR and LMR were negatively associated with hypertension prevalence in continuous analyses (1.060, 0.972-1.157; 0.926, 0.845-1.014; respectively), and the highest PLR and LMR tertiles (1.041, 0.959-1.129; 0.943, 0.866-1.028; respectively). Also, subgroup and sensitivity analyses indicated that SII had a greater correlation to hypertension. In conclusion, we find positive associations between SII and NLR and the prevalence of hypertension in this cross-sectional study. Our findings highlight that SII may be a superior systemic inflammation warning marker for hypertension.